Prognostic value of midtreatment FDG‐PET in oropharyngeal cancer. Issue 10 (4th April 2016) - Pollom, Erqi L.; Song, Jie; Durkee, Benjamin Y.; Aggarwal, Sonya; Bui, Timothy; von Eyben, Rie; Li, Ruijiang; Brizel, David M.; Loo, Billy W.; Le, Quynh‐Thu; Hara, Wendy Y.
Abstract: Background: Prognostic metabolic imaging indices are needed for risk stratification for patients with locally advanced oropharyngeal cancer. Methods: We retrospectively examined pretreatment and midtreatment fluorodeoxyglucose‐positron emission tomography (FDG‐PET) parameters in patients with locally advanced oropharyngeal cancer who were treated with definitive chemoradiation. Results: A total of 74 patients were evaluated. Pretreatment metabolic tumor volume (MTV) using threshold of 50% standardized uptake value (SUV) maximum (MTV50% ) was associated with progression‐free survival (PFS; p = .003; hazard ratio [HR] = 1.57 per 10 cc; 95% confidence interval [CI] = 1.17–2.11) and overall survival (OS; p = .01; HR = 1.36 per 10 cc; 95% CI = 1.07–1.74). Midtreatment MTV using a threshold of SUV 2.0 (MTV2.0 ) was associated with PFS ( p < .001; HR = 1.24 per 10 cc; 95% CI = 1.10–1.39) and OS ( p = .009; HR = 1.21 per 10 cc; 95% CI = 1.05–1.39). Nodal total lesion glycolysis (TLG) velocity >5% decrease/week was associated with improved PFS ( p = .04; HR = 0.37; 95% CI = 0.15–0.95). Conclusion: Metabolic response during chemoradiation is associated with survival in locally advanced oropharyngeal cancer and may aid with risk‐adapting treatment. © 2016 Wiley Periodicals, Inc. Head Neck 38: First–1478, 2016